Philosophy and Sociology Studies - S. A. Kravchenko; A. V. Shestopal (Vestnik MGIMO-Universiteta)
Philosophy and Social science school of MGIMO has received both nationwide and international recognition. The traditions of the school were laid by two highly respected scientists and science managers, George P. Frantsev, who was the rector MGIMO during the crucial period of its early years, and Alexander F. Shishkin, who was the founder and head of the Department of Philosophy. The former belonged to one of the best schools of antic history studies of the Petersburg (Leningrad) University. Frantsev made a great contribution to the restoration of Russian social and political science after World War II. After graduating from MGIMO, he worked at the Foreign Ministry of USSR, and then served as a rector of the Academy of Social Sciences and chief-editor of the journal "Problems of Peace and Socialism" in Prague. He consistently supported MGIMO scientists and recommended them as participants for international congresses and conferences. Shishkin was born in Vologda, and studied in Petrograd during 1920s. His research interests included history of education and morality. He was the author of the first textbook on ethics in the postwar USSR. Other works Shishkin, including monograph "XX century and the moral values of humanity", played a in reorienting national philosophy from class interests to universal moral principles. During thirty years of his leadership of the Department of Philosophy, Shishkin managed to prepare several generations of researchers and university professors. Scientists educated by Shishkin students consider themselves to be his "scientific grandchildren". The majority of MGIMO post-graduate students followed the footsteps of Frantsev in their research, but they also were guided by Shishkin's ideas on morality in human relations. Philosophy and Social science school of MGIMO played an important role in the revival of Soviet social and political science. Soviet Social Science Association (SSSA), established in 1958, elected Frantsev as its president, and G.V. Osipov as a deputy president. A year later Osipov became president and remained so until 1972.